PWE-149 The Efficacy and Safety of Treating Hepatitis C in Patients with a Diagnosis of Schizophrenia. (4th June 2013) - Mustafa, Z; Schofield, J; Mills, P R; Priest, M; Fox, R; Dutta, S; Morris, J; Forrest, E; Gillespie, R; Stanley, A J; Barclay, S
Abstract : Introduction: Treating hepatitis C with pegylated interferon alpha may induce or exacerbate psychiatric illness including depression, mania and aggressive behaviour. There is limited data regarding treatment in the context of chronic schizophrenia. We sought to establish the safety and efficacy of treatment of patients with a diagnosis of schizophrenia amongst patients attending treatment centres in Greater Glasgow Methods: Patient and treatment data collected on the Scottish hepatitis C database were retrospectively analysed according to the presence or absence of a diagnosis of schizophrenia. Combination antiviral therapy was defined as Interferon (pegylated or standard) and Ribavirin. Treatment outcomes including sustained viral response (SVR) rates, reasons for treatment termination and adverse events were documented Results: 5497 patients were recorded on the database, of whom 64 (1.2%) had a diagnosis of schizophrenia. Patients with and without schizophrenia were of similar age at diagnosis [median 34 (IQR 31–40) vs 36 (IQR 29–41) years, p = 0.85]. Patients with schizophrenia had higher rates of current or previous intravenous drug use [50/64 (78.1%) vs 3015/5433 (55.5%), p < 0.01] and prior alcohol excess > 21 units/week [25/64 (39%) vs 1211/5433 (22.2%), p = 0.02)]. More patients with schizophrenia had a diagnosis of cirrhosis [13/64 (20.3%) vs 589/5419 (10.86%), p = 0.02]. Of those patients who had attended at least one clinic appointment 1639/4415 (37.1%) of patients without schizophrenia commenced treatment versus 26/61 (42.6%) of patients with schizophrenia (p = 0.21). Patients with schizophrenia took almost three times as long to commence treatment after initial referral [median 1123 (IQR 531–2130) vs 421 (IQR 209–1086) days, p < 0.01], despite similar times from referral to first attendance [median 65 (IQR 36–141) vs 62 (IQR 35–130) days, p = 0.92] The treatment outcomes were as follows: Conclusion: Patients with stable schizophrenia are good candidates for hepatitis C treatment Disclosure of Interest: None Declared.